Risk factors for SARS-CoV-2 infection and epidemiological profile of Brazilian anesthesiologists during the COVID-19 pandemic: cross-sectional study - Luiz Guilherme Villares da Costa; Frederico de Lima Jacy Monteiro; Júlia Koerich de Souza; Verônica Neves Fialho Queiroz; Fábio de Vasconcelos Papa (Brazilian Journal of Anesthesiology, 2022)
Introduction: The devasting effects of COVID-19 have caused economic and health impacts worldwide. Anesthesiologists were one of the key professionals fighting the pandemic and have been highly exposed at their multiple sites of clinical practice. Thus, the importance of determining the nature of the infection in this population that provides care to SARS-CoV-2 patients. Method: We conducted a cross-sectional study administering an online questionnaire to examine the demographic and epidemiological profile of these professionals in Brazil, and to describe the risk factors for viral infection during the pandemic. Results: A total of 1,127 anesthesiologists answered the questionnaire, 55.2% were men, more than 90% with age below 60 years, with infection and reinfection rates of 14.7% and 0.5%, respectively, and 47.2% reported a significant income reduction. The predictors of COVID-19 contamination were practicing in operating rooms (OR = 0.42; 95% CI 0.23–0.78), direct contact with infected patients (OR = 5.74; 95% CI 3.05–11.57), indirect contact with infected patients (OR = 2.43; 95% CI 1.13–5.33), working in a pre-hospital setting (OR = 2.36; 95% CI 1.04–5.03), and presence of immunosuppression, except for cancer (OR = 4.89; 95% CI 1.16–19.01). Conclusion: COVID-19 had enormous consequences on Brazilian anesthesiologists regarding sociodemographic aspects and contamination rates (5.57 times higher than in the general population). These are alarming and unprecedented findings for this professional group, as they reveal the considerable risk of infection and its independent predictor variables.